A efetivação do direito à educação na Amazônia: um estudo sobre o financiamento do Ensino Médio no Estado do Pará - ALMEIDA, Edson de Sousa (Universidade Federal do Oeste do Pará, 2024)
This research assumes that education is a fundamental right of social character, deriving from the inherent dignity of the human person, and necessary for the emancipation of the human being, whose realization occurs from the elaboration and implementation of public policies (policy). From an interdisciplinary perspective between the areas of Education, Law and Public Policy, in order to shed light on the relationship between laws that posit a law and its effectiveness, the general objective of the research is to analyze how the financing of education provided for in the legal system influences the process of implementation of educational public policies aimed at the realization of this right. This research consists of an educational policy study that considers education as a mestizo and dialogic science by nature (Charlot, 2006), bringing to the discussion concepts from Legal Science as a way to enrich the debate around policy analysis. In terms of specific objectives, it was designed to define the necessary theoretical bases for the discussion of the theme; analyze the normative framework of the right to education and the financing of basic education at the federal and state levels; and the role of public policies as a tool for the realization of rights. The research comprised several methodological strategies, such as (i) bibliographic research, aiming to consolidate the theoretical framework about education as a fundamental human right of social nature and public policies as instruments that materialize the meaning of norms and enable the realization of rights; (ii) documentary research, based on the analysis of legislation and official documents related to the subject; and (iii) analysis of the object of study. Among other conclusions, there was a gap between what is foreseen in the legislation that deals with the financing of education and the implemented public policies aimed at guaranteeing the right to high quality education in the state of Pará, as well as the need for transfers. of resources directed to this right consider the geographical peculiarities of the federative entity, which impact on its effectiveness. The research indicates ways and contributions to the expansion of the possibilities of guaranteeing the realization of the right to basic education, specifically aimed at high school in the state of Pará.